A child with atypical teratoid/rhabdoid tumour of the posterior cranial fossa - Rahmat, K.; Kua, C.H.; Ramli, N. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
Primary central nervous system (CNS) atypical teratoid/rhabdoid tumours (ATRT) are highly malignant neoplasms which usually present in infancy or early childhood. Although ATRT may arise anywhere within the CNS, the majority (approximately two-thirds) arise in the cerebellum or posterior fossa, and the remainder in the cerebrum. We described the imaging characteristics of CNS ATRT in the posterior cranial fossa of a 14-month-old boy.